Undiagnosed Hypothyroidism as a Contributor to Cryptogenic Cirrhosis: A Case Report and Diagnostic Perspective - Hamdan, Angkasa Ramatuan; Handayani, Indri (Jurnal sosial dan sains, 2025)
Cryptogenic cirrhosis poses a diagnostic dilemma because its underlying cause remains unidentified. Emerging research indicates a two-way association between thyroid disorders—especially hypothyroidism—and liver disease. On one hand, liver dysfunction can impair thyroid hormone metabolism; on the other, hypothyroidism may play a role in advancing non-alcoholic fatty liver disease (NAFLD) and the development of cirrhosis. We report a case of a 48-year-old woman presenting with chronic diarrhea, cold intolerance, fatigue, jaundice, and easy bruising. There was no history of alcohol use, viral hepatitis, or other known causes of liver disease. Physical examination revealed bradycardia, psychomotor slowing, dry skin, and signs of liver dysfunction. Laboratory findings showed pancytopenia, elevated liver enzymes, hypoalbuminemia, and a thyroid profile consistent with overt hypothyroidism (low fT4 and elevated TSH). Imaging supported diagnoses of hepatic cirrhosis and benign thyroid nodules. The patient was treated with levothyroxine 100 mcg/day alongside supportive care. Within a few days, notable clinical improvement occurred, including cessation of diarrhea and better hematologic findings.. This case demonstrates that hypothyroidism may be overlooked as contributor to liver dysfunction, especially in cryptogenic cases. Considering the shared clinical manifestations and biochemical interplay between the liver and thyroid, it is important for clinicians to assess thyroid function in patients presenting with unexplained liver disease. Treating hypothyroidism in such contexts may lead to significant clinical improvement and may alter the course of hepatic deterioration.